2016
DOI: 10.5796/electrochemistry.84.784
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Photocatalytic Water Splitting Activity of Silver Tantalate by Photodeposited Platinum and Cobalt-Oxide Nanoclusters

Abstract: In this paper, we studied platinum (Pt)-and cobalt oxide (CoO x )-loaded silver tantalate (AgTaO 3 ) for photocatalytic overall water splitting. Pt and CoO x were loaded on AgTaO 3 by photodeposition, and the obtained photocatalysts were characterized by using powder X-ray diffraction (XRD), UV-visible (UV-vis) absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), inductively coupled plasma atomic emission spectroscopy (ICP-AES), and microscope inspection. By the scanning transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…84 To conclude, tantalate perovskites have received considerable focus compared to titanate and niobate active oxides due to the appropriate requisite conduction band edge (consisting of Ta 5d orbitals) for the generation of solar fuels. [85][86][87] However, the compounds of above mentioned ABO3 types are active under UV light and Silver Niobate (AgNbO3) (2.8 eV) has drawn some attention in photocatalysis due to its visible light response. 88 Such perovskite structured photocatalysts are composed of Ag 4d orbitals, far below the oxidation potential of water and therefore employed to split water under visible light in the presence of sacrificial agents.…”
Section: Ternary Oxide Photocatalystsmentioning
confidence: 99%
“…84 To conclude, tantalate perovskites have received considerable focus compared to titanate and niobate active oxides due to the appropriate requisite conduction band edge (consisting of Ta 5d orbitals) for the generation of solar fuels. [85][86][87] However, the compounds of above mentioned ABO3 types are active under UV light and Silver Niobate (AgNbO3) (2.8 eV) has drawn some attention in photocatalysis due to its visible light response. 88 Such perovskite structured photocatalysts are composed of Ag 4d orbitals, far below the oxidation potential of water and therefore employed to split water under visible light in the presence of sacrificial agents.…”
Section: Ternary Oxide Photocatalystsmentioning
confidence: 99%
“…They found that the overall water splitting reaction to H2 and O2 was realized by photodepositing Co-Pi as the oxidation catalyst and Pt as the reduction cocatalyst on an yttrium-doped BiVO4. Irie et al [164] reported that the overall water splitting activity of silver tantalate (AgTaO3) increased by 80 times when Pt and CoOx nanoparticles were photodeposited on the surface functioning as the H2 and O2 evolution cocatalysts, respectively. Further work [165] showed that the photodeposition of Pt and Co-Pi cocatalysts can also promote photocatalytic water splitting into H2 and O2 with a stoichiometric ratio over niobium-substituted AgTaO3.…”
Section: Photodeposition Of Earth-abundant Cocatalysts For Overall Wa...mentioning
confidence: 99%